Answer:
d = -12
Step-by-step explanation:
[tex]3i-4-di = -4-11i+2i\\3i-4-di = -4-9i\\3i-\left(4-di\right)-3i = -4-9i-3i\\-\left(4-di\right)=-4-12i\\\frac{- 4 - di}{-1} = -\frac{4}{-1}-\frac{12i}{-1}\\\frac{-\left(4-di\right)}{-1}\\= \frac{\left(4-di\right)}{1}\\=4-id\\=\frac{- 4 - 12i}{-1}\\=-\frac{- 4-12i}{1}\\=-( - 4)-( - 12i)\\=-\left(-4\right)-\left(-12i\right)\\= 4 + 12i\\4-(id) = 4 + 12i\\4 - id - 4 = 4 + 12i - 4\\- id=12i\\\frac{-id}{-i} = \frac{12i}{-i}\\\frac{id}{i}\\= d\\- \frac{12i}{i}\\= - 12[/tex]